2003
DOI: 10.1046/j.1365-2265.2003.01881.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of adrenocortical carcinoma

Abstract: Adrenocortical carcinoma (ACC) is a rare neoplasm with poor prognosis. Patients present with signs of steroid hormone excess (e.g. Cushing's syndrome, virilization) or an abdominal mass. Tumour size at presentation (mean diameter at diagnosis > 10 cm) is the most important indicator of malignancy. In addition, computed tomography (CT) typically demonstrates an inhomogeneous adrenal lesion with irregular margins and variable enhancement of solid components after intravenous contrast media. Magnetic resonance im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
174
2
22

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 193 publications
(202 citation statements)
references
References 152 publications
4
174
2
22
Order By: Relevance
“…Malignant neoplasias of the adrenal cortex account for 0.05-0.2% of all cancers, with an approximate prevalence of two new cases per million of population per year; adrenal cancer occurs at all ages, from early infancy to the eighth decade of life [21,22]. A bimodal age distribution has been reported, with the first peak occurring before age of 5 years, and the second in the fourth to fifth decade.…”
Section: Adrenal Cancer and Csmentioning
confidence: 99%
“…Malignant neoplasias of the adrenal cortex account for 0.05-0.2% of all cancers, with an approximate prevalence of two new cases per million of population per year; adrenal cancer occurs at all ages, from early infancy to the eighth decade of life [21,22]. A bimodal age distribution has been reported, with the first peak occurring before age of 5 years, and the second in the fourth to fifth decade.…”
Section: Adrenal Cancer and Csmentioning
confidence: 99%
“…ACC patients often present with clinical syndromes secondary to the production of corticosteroids, although some patients bear non-functioning neoplasms (Allolio et al 2004). The stage of the disease at diagnosis and complete surgical resection are recognized as the strongest predictors of long-term survival (Allolio et al 2004). In two large multicenter European series, it was found that approximately 20% of patients have metastatic disease at the time of presentation (Crucitti et al 1996, Icard et al 2001, one out of four patients is left with residual disease after operation and half of those who had an apparently radical resection eventually relapse, often with distant metastases (Crucitti et al 1996, Icard et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…ACC patients often present with clinical syndromes secondary to the production of corticosteroids, although some patients bear non-functioning neoplasms (Allolio et al 2004). The stage of the disease at diagnosis and complete surgical resection are recognized as the strongest predictors of long-term survival (Allolio et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of patients with ACC depends largely on surgical resectability [4]. An increasing number of adrenal tumors have been discovered because of technological advances in imaging modalities such as computed tomography (CT) and magnetic resonance imaging (MRI) [5], suggesting the possibility that an increasing number of smaller ACCs can be detected as adrenal incidentalomas.…”
mentioning
confidence: 99%